Process Optimization for Conversion Rate in NO Oxidation to NO2 over Co3O4 Catalyst - Muhammad Iqbal AlGhifari; Nailalthaf Putra Diarso; Jonathan Ivander Hutagaol; Muhammad Rafi Hafiyan Wibowo; Febriyanti Nurazizah; Edward Emmanuel Santosa (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
This study aims to evaluate the effect of flow rate and temperature variation on heat transfer performance in a heat exchange system. The analysis was conducted under steady-state conditions by examining key parameters, including heat transfer rate (Q), overall heat transfer coefficient (U), and logarithmic mean temperature difference (ΔTLMTD). In addition, dimensionless numbers such as Reynolds, Nusselt, and Prandtl were used to characterize the flow regime and convective heat transfer behavior under different operating conditions. The evaluation was carried out by analyzing the relationship between these parameters to understand the influence of operating variables on heat transfer characteristics. The results indicate that an increase in flow rate leads to improved heat transfer performance, as shown by higher values of U and enhanced convective heat transfer coefficients on both hot and cold fluid sides. This behavior is associated with increased turbulence intensity and a reduction in thermal boundary layer thickness, which promotes more effective heat transfer. However, deviations between theoretical and calculated values were observed, particularly on the cold fluid side. These deviations are influenced by changes in fluid properties, especially viscosity and thermal conductivity, which affect the Reynolds and Prandtl numbers. In general, the increase in flow rate results in higher Reynolds and Nusselt numbers, although a decrease in the Prandtl number was observed due to a more significant reduction in viscosity compared to thermal conductivity. Furthermore, increasing the inlet temperature of the hot fluid leads to a greater temperature difference between the hot and cold fluids, resulting in a higher logarithmic mean temperature difference (ΔTLMTD). Despite this increase, the overall heat transfer coefficient does not always show a proportional improvement, indicating the presence of non-ideal effects such as thermal resistance and possible fouling within the system. These findings demonstrate that heat transfer performance is influenced by the combined effects of flow rate, temperature variation, and fluid properties, and highlight the importance of considering these factors in evaluating and optimizing heat exchange processes. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).